The 3Ps: A tool for coach observation - Taylor, Jamie; MacNamara, Áine; Collins, Dave (Frontiers in Sports and Active Living, 2023)
Across sporting contexts, there is growing recognition of the value of ‘in situ’ coach development practice. Unfortunately, however, there remains a limited number of tools available to observe coaching practice. In this study we pilot and test a quasi-systematic tool for observation in the form of the 3Ps. Drawing on a range of representational perspectives the theoretically neutral labels of Procedure, Planning and Process were developed for the purpose of holistic observation. In testing the tool, a group of experienced coach development practitioners (n=10) integrated the tool in their practice over a 12-month programme of professional development. Subsequently, participants took part in semi-structured interviews, articulating a universal sense of acceptability through perceptions of effectiveness and positive opportunity cost. We suggest the 3Ps present a holistic and practically useful means of observing coaches’ Professional Development and Decision Making. We also suggest future directions for the researcher seeking to generate evidence in the naturalistic coaching context.